2021
DOI: 10.1021/acs.biomac.1c00465
|View full text |Cite
|
Sign up to set email alerts
|

Biomass Shape Memory Elastomers with Rapid Self-Healing Properties and High Recyclability

Abstract: Biomass bifunctional polyamide elastomers (BbPEs) were successfully prepared from dimer acid (DA), trimer acid (TA), and triethylenetetramine with shape memory and self-healing abilities. In the composition structure of BbPEs, vast hydrogen bonds formed among the amide bonds of different segments endowed the BbPEs with self-healing ability. At room temperature, the mechanical properties of BbPEs can be restored to 49% of the original condition after healing for 2 h. In addition, the physical and chemical cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…It is worth noting that S-cPDs present a terrific mechanical strength and elastic recovery ratio in comparison with other reported PAEs (Figure e and Table S5). …”
Section: Resultsmentioning
confidence: 99%
“…It is worth noting that S-cPDs present a terrific mechanical strength and elastic recovery ratio in comparison with other reported PAEs (Figure e and Table S5). …”
Section: Resultsmentioning
confidence: 99%
“…In the case of the shape memory process, the deformation of a material after 5 min of recovery time returned to about 95% of the original shape. The phenomenon indicated that the internal segments in materials can rapidly respond to temperature changes and accelerate the recovery to their original shape [55]. Furthermore, another example by Li et al [86] confirmed the effect of temperature on the self-healing process of shape memory elastomers as shown in Figure 9.…”
Section: Self-healing Shape Memory Elastomersmentioning
confidence: 78%
“…Moreover, for thermoplastic elastomers, a market research report by MarketsandMarkets™ revealed that the market was worth USD 5.1 billion in 2021, with a compound annual growth rate of 5.8% between 2021 and 2026 (Table 3). [ [50][51][52][53] Poly(ether-b-amide) Moisture Biomedical and industrial applications [54] Polyamide elastomers Thermal Self-healing materials, Intelligent electronic devices, Bionic materials [55] SMEs such as polyurethane and natural rubber typically comprise two regions: amorphous and crystalline. The amorphous region supports the stabilisation and retention of the original shape, and then the deformation of this region induces shape recovery.…”
Section: Polymermentioning
confidence: 99%
See 1 more Smart Citation
“…Temperatures at 0 and 60 C Shape recovery reaches 95% in 5 min. The recovery efficiency is 88.9% [242] Advanced manufacturing technology has been introduced in the structural design at the macroscopic level. This technology encompasses several methods to manufacture elastomeric samples in three and four dimensions.…”
Section: Discussionmentioning
confidence: 99%